2015
DOI: 10.1590/1678-775720150075
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α, TNF-β and IL-10 gene polymorphism and association with oral lichen planus risk in Saudi patients

Abstract: Objectives Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disease. Cytokines play an important role in the pathogenesis and disease progression of OLP. Various reports have implicated cytokine gene polymorphisms in susceptibility to develop some immune mediated conditions including OLP. The purpose of this study was to investigate the association of tumor necrosis factor (TNF)-α, TNF-β and interleukin (IL)-10 gene polymorphisms with the OLP risk.Material and Methods Forty two unrelated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 31 publications
4
42
0
1
Order By: Relevance
“…The total number of studies related to the SNP of ILs is shown in Table S2. Eventually, 6 studies [1820,2426] including 4 SNPs (IL6-174G/C, IL10-592C/A, IL10-819C/T, and IL10-1082G/A) meeting the inclusion criteria were included for the ultimate quantitative analysis. All of the SNPs of ILs which were not analyzed in this meta-analysis were concluded in qualitatively in Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of studies related to the SNP of ILs is shown in Table S2. Eventually, 6 studies [1820,2426] including 4 SNPs (IL6-174G/C, IL10-592C/A, IL10-819C/T, and IL10-1082G/A) meeting the inclusion criteria were included for the ultimate quantitative analysis. All of the SNPs of ILs which were not analyzed in this meta-analysis were concluded in qualitatively in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Of these included studies, a total of 362 OLP patients and 622 non-OLP control subjects from 5 different countries were covered. Three of 6 studies [18,25,26] focused on the SNP of IL6-174G/C, whereas 4 of 6 studies [19,20,2426] focused on IL10-592C/A, IL10-819C/T, and IL10-1082G/A, respectively. The characteristics of the included studies, including the P value for HWE and quality assessment are summarized in Table 1 and S3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, OLP has been reported to be associated with systemic medical conditions, such as diabetes, hepatitis C viral infections, hypertension, ulcerative colitis, myasthenia gravis and lupus erythematosus (2,3,4,11). Recently, several studies have revealed the genetic susceptibility of OLP through case control association testing (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α (-308) promoter polymorphism leads to a less common allele-A (allele 2), which has been associated with increased TNF-α production in vitro [33,34] and higher rate of TNF-α transcription than wild-type GG genotype [35,36]. This polymorphism has been linked to increased susceptibility to several chronic metabolic degenerative, inflammatory and autoimmune diseases [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%